The Influence of Work Environment and Motivation on Work Discipline of Grand Rocky Hotel Bukittinggi Employees - Alfajar, Mhd; Abrian, Youmil (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The purpose of this study was to see and measure how much influence the work environment (X1) and motivation (X2) had on the work discipline (Y) of employees at Grand Rocky Hotel Bukittinggi. The author uses a quantitative descriptive research method and the approach is causal associative. The technique for collecting data from the sample using a questionnaire has been tested for validity and reliability, distributed to employees of Grand Rocky Hotel Bukittinggi. In this study, the determination of the sample used proportional random sampling technique with a total of 82 samples. The data collected was processed using the SPSS application on a computer. To determine the assessment of the data by conducting normality testing, heteroscedasticity testing, multicollinearity testing. To find out the relationship between variables by doing multiple linear regression testing. After processing the data, this study states that the work environment has no influence on employee work discipline with the acquisition of the number of sig. 0.176 > 0.05, while motivation has a significant effect on work discipline with a sig. 0.000 < 0.05. But together the work environment and motivation affect work discipline with the acquisition of sig. 0.000 < 0.05. But together the work environment and motivation affect work discipline with the acquisition of sig. 0.000 < 0.05. But together the work environment and motivation affect work discipline with the acquisition of sig. 0.000 < 0.05.